Cumulative Prong Counts in Electron Neutrino Appearance Data as a Probe of Hierarchy and Dirac Phase - Glenny, Dalton L. (Tufts Archival Research Center, 2021)
This Thesis develops a new approach for determining values for neutrino oscillation parameters using ”prong counting.” The method is shown to replicate those obtained by a conventional, more elaborate analysis carried out by the NOvA neutrino oscillation experiment.; An Honors Thesis for the Department of Physics and Astronomy